Perancangan Service Catalogue Pada Layanan IT Di Industri Pulp and Paper Divisi Teknikal Dokumen Kontrol Berdasarkan Framework ITIL Versi 3 - Lestari, Indri Endang; Cholil, Widya; Antoni, Darius; Syamsuar, Dedy; Akbar, Muhammad (P3M Politeknik Negeri Banjarmasin, 2021)
IT services are one of the important factors in business operations in the technical document control division. The document control technical division is a division that has a vital role in supporting the construction, production and maintenance processes. This study aims to design a service catalog management using the ITIL V3 framework. The stages in designing this catalog are problem identification, data collection, data analysis, domain mapping based on the ITIL version 3 framework, domain determination, and e-catalog management design. And this research produces an e-catalog management application that contains information about the service descriptions in the technical division of document control and management of incidents that occur.